(untitled) (Technological Innovations Journal, 2024)
Objective: To identify the main elements that give rise to school bullying and address the issue of bullying within current education. Method: A qualitative approach was adopted, which included a systematic review based on the PRISMA methodology. An exhaustive analysis of information was conducted using the databases: Scielo, EBSCO, Psycnet, PubMED, PsycInfo, Dialnet, and the Education Resources Information Center (ERIC), yielding 12 primary articles. The selected identifiers were: "bullying," "educational environment," "education," "interpersonal skills," "psychopedagogy." The work was carried out during the months of August, September, and October 2024. Results: Among the main elements that give rise to school bullying are the family’s psycho-affective development history, hereditary and predisposing factors for aggression, historical-socio-cultural environment, gender identity, and disabilities, which should be addressed through cognitive-behavioral therapy, emotive-rational therapy, and an ecological-philosophical approach. Conclusion: The presence of these negative elements within the psychological, social, educational, cultural, and global development fields of contemporary society implies a setback in terms of human rights and personal freedom, as it conditions and aggresses an individual’s sense of self in various ways.